Growth and Nutritive Value of Three Old World Bluestems and Three Legumes in the Semiarid Texas High Plains. Issue 1 (1st January 2013) - Cui, Song; Allen, Vivien G.; Brown, C. Philip; Wester, David B.
Abstract : Benefits of legume–grass mixtures are well known but water required for legume growth limits use in semiarid, irrigation‐dependent environments. Research conducted over 4 yr (2007 to 2010) in the semiarid Texas High Plains compared alfalfa ( Medicago sativa L.), yellow sweetclover [ Melilotus officinalis (L.) Lam.], and sainfoin ( Onobrychis viciifolia Scop.) interseeded into three old world bluestems ( Bothriochloa spp.). No fertilizer N (control) and 60 kg N ha −1 treatments were applied to grasses alone. The five treatments imposed on each grass were replicated three times in a randomized complete block design with the legume and N treatments in a split‐plot arrangement. Irrigation water applied through subsurface drip was limited to 250 mm annually. Annual dry matter yield of grass monocultures exceeded grass–legume mixtures in year 1 but yield of grass–legume mixtures was similar to N fertilizer in subsequent years. Crude protein (CP) and dry matter digestibility (DMD) were higher while cell wall was lower in the mean of grass–legume mixtures than grass monocultures. Nitrogen fertilization increased CP but had little effect on cell wall or DMD (g kg −1 ). Nutritive value benefits from yellow sweetclover occurred in year 1 and then declined while benefits from alfalfa increased over 4 yr. Lower sainfoin stands limited nutritive value. With limited irrigation, benefits of including legumes can exceed 60 kg N ha −1 in this semiarid environment.